2023
DOI: 10.1007/s00167-022-07302-x
|View full text |Cite
|
Sign up to set email alerts
|

Significant changes in lower limb alignment due to flexion and rotation—a systematic 3D simulation of radiographic measurements

Abstract: Background Many radiographic lower limb alignment  measurements are dependent on patients’ position, which makes a standardised image acquisition of long-leg radiographs (LLRs) essential for valid measurements. The purpose of this study was to investigate the influence of rotation and flexion of the lower limb on common radiological alignment parameters using three-dimensional (3D) simulation. Methods Joint angles and alignment parameters of 3D lower limb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In zero position, mean value for HKA angle was 180.1° (SD: ± 3.1°) and for the MPTA angle 87.7° (SD: ± 2.6°). The mean mechanical axis deviation (MAD) was measured to be 6.2 mm (SD: ± 8.4 mm), which is also within the range reported by Paley et al as the physiological norm (10 mm ± 7 mm) [2, 17, 18]. Exclusion criteria were advanced osteoarthritis of the hip or knee joint, radiographic evidence of previous realignment surgery, fractures, and any lower extremity joint replacement.…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…In zero position, mean value for HKA angle was 180.1° (SD: ± 3.1°) and for the MPTA angle 87.7° (SD: ± 2.6°). The mean mechanical axis deviation (MAD) was measured to be 6.2 mm (SD: ± 8.4 mm), which is also within the range reported by Paley et al as the physiological norm (10 mm ± 7 mm) [2, 17, 18]. Exclusion criteria were advanced osteoarthritis of the hip or knee joint, radiographic evidence of previous realignment surgery, fractures, and any lower extremity joint replacement.…”
Section: Methodssupporting
confidence: 62%
“…However, the determination of angles in LLRs is highly sensible to rotational inluence and prone to error, as several previous studies have demonstrated a signiicant decrease in medial proximal tibial angle (MPTA) and hip-knee joint angle (HKA) due to rotation [1,2,7]. In particular, deformities, osteoarthritis, and restricted mobility in general result in malrotation between 20° of external and internal rotation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators mostly performed standard digital long-leg radiographs [13,23,25,26]. Here, torsional malalignments, extension deficits of the knee joint and inaccurate adjustment of the projection plane led to measurement errors, which could be prevented by using EOS imaging [2,17].…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative planning was performed using a specific software by one manufacturer and based on manually determination of bony landmarks in preoperative NWB CT. By using standardised definitions for each landmark the reliability to obtain reproducible alignment parameters is high, but cannot simply be transferred to all 3D models [ 20 ]. Preoperative passive extension deficit was considered as clinical parameter, since extension deficits of the knee can significantly influence the coronal lower limb alignment especially in combination with (mal‐)rotation [ 33 , 35 , 36 ]. The differences between planned and achieved (postoperative) coronal correction as well as the influence of the surgeon dependent adjustment was not part of this study.…”
Section: Discussionmentioning
confidence: 99%